2019
DOI: 10.3399/bjgp19x704633
|View full text |Cite
|
Sign up to set email alerts
|

Provision and accessibility of primary healthcare services for people who are homeless: a qualitative study of patient perspectives in the UK

Abstract: BackgroundAnecdotal reports of people who are homeless being denied access and facing negative experiences of primary health care have often emerged. However, there is a dearth of research exploring this population’s views and experiences of such services.AimTo explore the perspectives of individuals who are homeless on the provision and accessibility of primary healthcare services.Design and settingA qualitative study with individuals who are homeless recruited from three homeless shelters and a specialist pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
145
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 97 publications
(148 citation statements)
references
References 17 publications
3
145
0
Order By: Relevance
“…Stigma and discrimination were also commonly cited in relation to societal attitude towards homelessness and people experiencing homelessness. However, previous research showed that people experiencing homelessness also face stigma and discrimination when accessing health services (Paudyal et al 2018 ; Gunner et al, ). Anti‐stigma interventions for healthcare professionals such as the ‘targeting the roots of healthcare provider stigma’ which involves improving the ability of healthcare professionals to cope with the feelings and emotions when working with vulnerable patients; improving their competence and the confidence of staff; and addressing the lack of awareness of one's own prejudices have been shown to minimise perceived stigma and discrimination (Knaak & Patten, ).…”
Section: Practice and Research Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Stigma and discrimination were also commonly cited in relation to societal attitude towards homelessness and people experiencing homelessness. However, previous research showed that people experiencing homelessness also face stigma and discrimination when accessing health services (Paudyal et al 2018 ; Gunner et al, ). Anti‐stigma interventions for healthcare professionals such as the ‘targeting the roots of healthcare provider stigma’ which involves improving the ability of healthcare professionals to cope with the feelings and emotions when working with vulnerable patients; improving their competence and the confidence of staff; and addressing the lack of awareness of one's own prejudices have been shown to minimise perceived stigma and discrimination (Knaak & Patten, ).…”
Section: Practice and Research Implicationsmentioning
confidence: 99%
“…TDF has been used extensively in qualitative studies to identify target behaviours for future interventions and to characterise implementation problems (Atkins et al, 2017;Cane et al, 2012). The researchers have previously used TDF in qualitative studies in identifying barriers of: access to primary healthcare by persons experiencing homeless (Gunner et al, 2019) and effective transition of care of such persons across services (Smith, Paudyal, MacLure, et al, 2018). When using TDF, it is imperative that the framework is used from the outset, including the development of an interview schedule, as the use of TDF at later stages of the research provides challenges in mapping the data against TDF domains (Atkins et al, 2017;Cane et al, 2012).…”
Section: Pillars Of Self-carementioning
confidence: 99%
See 1 more Smart Citation
“…Well‐supported general practice may have the potential to contribute to improving the health and well‐being of people experiencing homelessness because of its emphasis on care coordination, the doctor–patient relationship and whole person care (RACGP, ). It has also been suggested, however, that inadequate general practice care may be contributing to an ineffective and inefficient healthcare system response to people experiencing homelessness (Gunner et al, ). To ensure that general practice approaches to healthcare provision are effective, welcoming and trauma‐informed rather than utopian, dismissive or stigmatising, these services need to be guided by the voices and ‘insider perspectives’ of service users.…”
Section: Introductionmentioning
confidence: 99%
“…To ensure that general practice approaches to healthcare provision are effective, welcoming and trauma‐informed rather than utopian, dismissive or stigmatising, these services need to be guided by the voices and ‘insider perspectives’ of service users. Given the dearth of such voices (Gunner et al, ), the aim of this study was to explore the experiences and attitudes of homeless men regarding community‐based healthcare, and general practice in particular, to identify the potential areas for improvement .…”
Section: Introductionmentioning
confidence: 99%